ANALISIS SOAL TES BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA BILANGAN CACAH KELAS IV DI SD NEGERI 104218 SIDOMULYO - Panjaitan, Riza Wita; Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this research was to determine the validity, reliability, difficulty level, discriminating power, and distractor effectiveness of 15 multiple-choice mathematics questions on whole numbers for Grade IV students at SDN 104218 Sidomulyo. This research employed a quantitative descriptive method. The population consisted of 42 students, while the sample included 23 students. The research instrument was a set of 15 multiple-choice mathematics questions on whole numbers for Grade IV. Data analysis was conducted using SPSS Software and Microsoft Excel. The research findings indicate that 5 questions (33.3%) were valid, while 10 questions (66.7%) were invalid. The test instrument scored < 0.6, making it unreliable. All 15 questions had a moderate difficulty level. The discriminating power of the test items varied, with 4 questions classified as very poor, 6 questions as poor, 3 questions as fair, and 2 questions as good. Regarding the effectiveness of the distractors, only a few items required revision, and only one option was rejected or replaced.